Methodologies of Design in the Field of Visual Communication and Digital Media - Huseynova, Humeyra (InterConf. Scientific Collection, 2026)
To summarize. The purpose of this study piece is to explore the primary design strategies and systemic issues that have an impact on the efficiency of visual communication in digital media. Within the scope of this research, topics pertaining to responsive design, information overload, navigation dysfunction, diminished brand identification, and the influence of artificial intelligence on creative processes are thoroughly examined.